1966
DOI: 10.2135/cropsci1966.0011183x000600060008x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Measures of Earliness of Crop Maturity in Cotton1

Abstract: Certain features of the gross morphology of the cotton plant furnish clues to earliness of crop production. Three such features — (1) node of first fruiting branch (NFB), (2) number of vegetative branches (NVB), and (3) percentage of bolls on vegetative branches (PBV) — were used as morphological measures of earliness in the studies reported here. All of the morphological measures were significantly correlated but, because of its higher heritability and lower variability, NFB is considered the most reliable an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 0 publications
4
26
0
1
Order By: Relevance
“…. Involvements of both additive and non-additive gene effects have been reported in cotton by many workers [2] . Early maturity protects cotton from frost damage, insect and disease buildups, escape pink bollworm and fertilizer and insecticide application, soil moisture depletion, less number of irrigation, decreased higher quality and leave field for the next cultivation.…”
Section: Introductionmentioning
confidence: 94%
“…. Involvements of both additive and non-additive gene effects have been reported in cotton by many workers [2] . Early maturity protects cotton from frost damage, insect and disease buildups, escape pink bollworm and fertilizer and insecticide application, soil moisture depletion, less number of irrigation, decreased higher quality and leave field for the next cultivation.…”
Section: Introductionmentioning
confidence: 94%
“…Both populations segregated for NFB, an indirect measure of Xowering time (Ray and Richmond 1966;Low et al 1969). Similar to commercial cultivars, once an F 2 plant produced a fruiting node, it usually continued to produce fruiting branches at each succeeding main stem node.…”
Section: Flowering Responsementioning
confidence: 99%
“…By comparing with diVerent measurements of earliness in cotton, Ray and Richmond (1966) concluded that NFB was the most reliable and practical measurement. Considering the heritability and correlation with Wnal picking, Low et al (1969) also suggested using NFB as a criterion to measure earliness.…”
Section: Introductionmentioning
confidence: 99%
“…Earliness is a primary breeding objective of cotton breeders (Braden and Smith, 2004). Its indeterminate growth habit has been adapted to annual cultivation due to enormous efforts of cotton breeders (Ray, 1966). Alleviating from some growth delaying environmental and managing factors in cotton are the most important traits in the earliness cotton cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Divided leaves allow sunlight to penetrate deeper into the canopy, which improves early boll set. Varieties with lower root/shoot rations expend less carbohydrate on soil exploration which can enhance earliness if coupled to early because of heat and drought stresses (Ray, 1966). The row to row distance was maintained at 0.8m whereas plants within rows were thinned out to maintain a distance of 0.2m between plants.…”
Section: Introductionmentioning
confidence: 99%